Review of the millipede genus Hyleoglomeris Verhoeff, 1910 in China, with descriptions of new species (Diplopoda, Glomerida, Glomeridae) - Golovatch, Sergei I.; Liu, Weixin; Geoffroy, Jean-Jacques (Zootaxa, 2012)
China is shown to currently support 23 species of the large, basically warm temperate to tropical Asian genus Hyleoglomeris,all keyed and mapped, including 15 new ones: H. tiani sp. n., H. xia sp. n. and H. youhao sp. n. from Hunan Province, H. wusesp. n., H. nigu sp. n., H. gudu sp. n. and H. yinshi sp. n. from Guizhou Province, as well as H. qiyi sp. n., H. lii sp. n., H.heshang sp. n., H. xueju sp. n., H. mulunensis sp. n., H. mashanorum sp. n., H. curtisulcata sp. n. and H. kunnan sp. n. fromGuangxi Province. Hyleoglomeris eusulcata Golovatch, Geoffroy & Mauriès, 2006 has been recorded and redescribed from anew, near-topotype sample. Two new species groups are being proposed: the venustula- and the albicorporis-group. The statusof Nearctomeris Wesener, 2012, a monobasic genus from the eastern USA, is questioned viz-à-viz Hyleoglomeris, albeit no formal synonymy is being proposed.